Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Panitia Pemungutan Suara (PPS) di Komisi Pemilihan Umum (KPU) Kota Jakarta Barat - Hindriari, Reni; Khair, Oki Iqbal; Sunardi, Sunardi; Munadjat, Baliyah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to analyze the influence of organizational culture and work motivation on the performance of the Voting Committee (PPS) in the General Election Commission (KPU) of West Jakarta. Additionally, it seeks to determine which variable has the most dominant impact on PPS performance. This research employs an associative method with a quantitative approach. The population consists of all 168 PPS members in West Jakarta, with a sample of 63 respondents selected using Slovin’s formula from 56 urban villages. Data collection methods include questionnaires, interviews, and documentation. Data analysis is conducted using descriptive statistics and inferential analysis through regression modeling with SPSS version 25. Organizational culture comprises values, beliefs, norms, and behaviors that define work and interaction within an organization. A strong organizational culture enhances work motivation, which refers to factors driving individuals to perform well, either through internal aspirations or external recognition. Increased work motivation positively impacts PPS performance, which reflects efficiency, productivity, and job quality. A supportive organizational culture, high motivation, and a fair reward system contribute to improved PPS performance, benefiting both the organization and the community. The alignment between organizational culture, work motivation, and PPS performance is crucial in optimizing service delivery and achieving organizational goals.